preparation Kindergarten curriculum in accordance requirements Sustainable Development (Journal of the College of Basic Education, 2022)
Today's world faces many challenges that are increasingly concerned about its negative implications for the future of the world, and there is an urgent need for future planning that will prevent future problems for future generations. The importance of kindergartens and their curricula is that they deal with children at a very early stage in their lives. They are the stage of rapid overall growth, in which the mental powers of children are opened, and the motivation of their cognitive curiosity is markedly demonstrated by the fact that they are trying to get close to everything , And senses the windows that are overlooking the environment around them to know them and improve the handling and adaptation. Global attention to early childhood education for sustainability has increased, and many international organizations have recommended that education for sustainable development should be activated at the kindergarten stage, particularly through the formal or national curriculum within UNESCO's "Reorientation towards Sustainability" . This has prompted the two researchers to discuss the preparation of the curriculum of kindergartens according to the requirements of sustainable development in order to keep abreast of developments and recent developments in the field of education. The researchers have noticed that there are serious Arab approaches towards achieving this goal, but they have not lived up to the ambition. In such topics in order to develop the curricula of kindergartens to take the leading role in providing children with the skills, concepts and experiences that lead to smooth handling of the latest developments of the age, and concluded the study to a number of recommendations and proposals.